Human Resources Management Examines itself and its Limitations - Barkin, Solomon (Relations industrielles / Industrial Relations, 1989)
In the present paper, the author is analysing and criticizing the prevalence of human resources management (HRM) in the study of industrial relations over the past few years, as shown in a previous article of this journal. This controversial topic is subject to discussion and exchange of views which can be sustained through this forum.